Water Quality Parameters and Sanitation Status of the Educational Institutions at Jamurki, Mirzapur, Tangail - Hoque, MM; Miah, AK; Rahman, MS; Rahaman, MS; Hossain, MK (Journal of Environmental Science and Natural Resources, 2015)
The study was conducted to investigate the water quality parameters and sanitation status in the educational institutions at Jamurki Union in Mirzapur of Tangail district. The study determined different water quality parameters such as As, pH, Fe, DO, TDS and EC. Most of the investigated water quality parameters in the study area were suitable for drinking purposes comparing with standard values. The range of investigated parameters in the study area of educational institutions were As 0 to 15 ppb, pH 6.5 to 8.5, Fe 0.1 to 0.9 ppm, DO 2.5 to 4.0 mg, TDS 121 to 445 ppm, EC 246 to 592 ?s/cm and most of the color of water samples water were standard means colorless and the odor of samples were also good However, the values of pH was exceeded somewhere. All of the tube wells were free from Arsenic. Most of the samples exceeded the standard values of Fe. The study identified the various problems of sanitation systems in the educational institutions e.g. Poor sanitation condition, dirty toilets, and insufficient toilets for female students. J. Environ. Sci. & Natural Resources, 8(1): 121-124 2015